What future for the child after COVID-19 - Giovanna Perricone (Hygeia Press di Corridori Marinella, 2022)
This paper studies the possible condition of fragility as a "dysfunctional psychophysical state" of the child in these times of SARS-CoV-2, based on neuroscientific studies, a biopsychological approach and on know-how from pediatric psychology. We bring to your attention a possible interventional approach for the support, orientation, accompaniment and shadowing of the child which has experienced and is still living through the pandemic, to allow the child to reverse the developmental risk that the COVID-19 pandemic constitutes. This period experienced by the child has taken on the meaning of a "developmental emergency", the importance of which depends on relations between disorders (caused by the state of fragility which exposure to the adverse event can determine) and the developmental resources available to the child.  This "ferrying" must necessarily include the management of the child as a "field", bringing into play know-how from pediatric psychology. It is a "field" which is constituted by the outcome of relationships the child has with his/her reference system. For the professional figures involved, managing the field means intervening in all the types of relationships which define it. This is done through proximal, community-based interventions, promoting strengthening actions, such as reinforcing life skills, and, therefore, improving the developmental trajectory. This provides support to the child when facing transformation developmental tasks created by the developmental crisis which the pandemic, as a critical event, has determined.